2021
DOI: 10.3389/fcell.2021.621810
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Cell Surface Biotinylation and SILAC-Based Quantitative Proteomics Identified Myoferlin as a Potential Therapeutic Target for Nasopharyngeal Carcinoma Metastasis

Abstract: Distant metastasis is a major cause of treatment failure in nasopharyngeal carcinoma (NPC) patients. Cell surface proteins represent attractive targets for cancer diagnosis or therapy. However, the cell surface proteins associated with NPC metastasis are poorly understood. To identify potential therapeutic targets for NPC metastasis, we isolated cell surface proteins from two isogenic NPC cell lines, 6-10B (low metastatic) and 5-8F (highly metastatic), through cell surface biotinylation. Stable isotope labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…ZBTB7A, or Pokemon, showed complex characteristics and was expressed at different levels in NPC cells. 5-8F and 6-10B cells were used as the research objects because of their high and low metastatic potential, respectively (Li et al, 2021). WB assays showed that ZBTB7A expression in 5-8F was higher than in 6-10B cells (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ZBTB7A, or Pokemon, showed complex characteristics and was expressed at different levels in NPC cells. 5-8F and 6-10B cells were used as the research objects because of their high and low metastatic potential, respectively (Li et al, 2021). WB assays showed that ZBTB7A expression in 5-8F was higher than in 6-10B cells (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics can analyze the dynamics of protein composition, expression level, and modification status in the organism from a holistic perspective by comparing different proteins, understanding protein-protein interaction (PPI) and linkage, and revealing the pattern of protein function and life activity. Essential for understanding the development, prevention, diagnosis, and treatment of cancer [2].…”
Section: The Research Content and Significance Of Proteomicsmentioning
confidence: 99%
“…13,16 Additionally, overexpression of MYOF accelerates the process of epithelial−mesenchymal transition (EMT) to promote the invasion and metastasis of cancer cells, and inhibition of MYOF induces the transition of mesenchymal cells to the epithelial cells. 11,19,20 Briefly, MYOF plays a vital role in various tumors and is becoming an emerging cancer therapeutic target. Since the full-length protein crystal structure of MYOF has not been revealed yet, the studies for developing novel MYOF inhibitors are encountering more challenges.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, recent studies demonstrated that MYOF was lowly expressed in normal cells but highly expressed in various malignant tumors such as gastric cancer, , breast cancer, , colon cancer, pancreatic cancer, , B-cell lymphoma, and liver cancer . At the same time, the high expression of MYOF significantly reduced the survival time of patients and was strongly correlated with poor prognosis. , Additionally, overexpression of MYOF accelerates the process of epithelial–mesenchymal transition (EMT) to promote the invasion and metastasis of cancer cells, and inhibition of MYOF induces the transition of mesenchymal cells to the epithelial cells. ,, Briefly, MYOF plays a vital role in various tumors and is becoming an emerging cancer therapeutic target.…”
Section: Introductionmentioning
confidence: 99%